Cervical Spine In Psoriasis - Banerjee Kalya; Banerjee Raghubir; Biswas T.K; Paul R.N; Singh D (Wolters Kluwer Medknow Publications, 1995)
Clinical study and X-ray of the cervical spine from patients with psoriasis and psoriatic arthritis were compared with similar films from a control population. Evidences suggest that neck is involved in psoriasis similar to those described for spondylitis. Apophyseal narrowing is 60% compared to 20% in control, apophyseal sclerosis is 40% compared to 15% in control, and an apophyseal calcification of anterior ligaments is 25% compared to 10% in control.